Effects of biochar on nitrogen transformation and heavy metals in sludge composting. (July 2017) - Liu, Wei; Huo, Rong; Xu, Junxiang; Liang, Shuxuan; Li, Jijin; Zhao, Tongke; Wang, Shutao
Highlights: This study explored the effect of different biochar additions on sewage sludge. Biochar amendment was beneficial to passivation of heavy metals in the compost pile. The treatment with 5% biochar is suggested for sludge composting to enhance quality. Abstract: Composting is regarded as an effective treatment to suppress pathogenic organisms and stabilize the organic material in sewage sludge. This study investigated the use of biochar as an amendment to improve the composting effectiveness and reduce the bioavailability of heavy metals and loss of nitrogen during composting. Biochar of 0%, 1%, 3%, 5% and 7% were added into a mixture of sludge and straw, respectively. The use of biochar, even in small amounts, altered the composting process and the properties of the end products. Biochar addition resulted in a higher pile temperature (66 °C) and could reduce nitrogen loss by transforming ammonium into nitrite. In the 5% biochar group, the final product from sludge composting, ammonia nitrogen, decreased by 22.4% compared to the control, and nitrate nitrogen increased by 310.6%. Considering temperature and N transformation, the treatment with 5% biochar is suggested for sludge composting.